Does the renal portal valve exist in a raptor species? A study aimed at further evaluating the mechanism of toxicity of diclofenac in vultures. (30th June 2020) - Havenga, Lauren; Naidoo, Vinny; Wolter, Kerri; Duncan, Neil; Groenewald, Hermanus B.
Abstract: Diclofenac has been responsible for the deaths of millions of vultures on the Asian subcontinent. While the pathology of toxicity is well described, the mechanism of toxicity remains elusive. However, it was postulated that toxicity could be related to the unique avian renal vascular structure known as the renal portal valve and that that diclofenac altered valve functionality with subsequent renal ischaemia. While plausible, the valva renalis portalis has only been described in a small number of other bird species such as the chicken ( Gallus domesticus ), the domestic duck ( Anas platyrhynchos domesticus ) and ostrich ( Struthio camelus ) but not a raptor. The aim of this study was to evaluate the renal anatomy and related vasculature of the Cape griffon vulture ( Gyps coprotheres ) (CGV), a species sensitive to the toxic effects of diclofenac, using gross anatomy, histology and vascular casting. The vasculature of the vulture was found to be almost identical to that of the domestic chicken with the valva renalis portalis present in the v. iliaca externa between the v . renalis renalis cranialis and the v . renalis caudalus . The valve was ring‐shaped with finger‐like processes and histologically was composed of smooth muscle. The valve was also well vascularized and was associated with a nerve plexus. Based on the findings of this study, the proposed mechanism of toxicity is anatomically possible.